Strategi implementasi Adiwiyata di SDN 1 Kota Bengkulu melalui Kegiatan Gotong Royong - Ady Darmansyah; Atika Susanti (Sangkalemo : The Elementary School Teacher Education Journal, 2023)
Increasing environmental awareness in Adiwiyata schools encourages students to have a high level of consciousness about the importance of the environment and take tangible actions to protect it. These activities include learning about nature, waste management, energy conservation, and other conservation efforts. This research aims to analyze the implementation strategies of the Adiwiyata program in elementary school 1 Bengkulu city through communal activities. The study is conducted using a qualitative approach and a case study method. Data is collected through observation, interviews, and document analysis. The research findings indicate that elementary school 1 Bengkulu city has implemented the Adiwiyata program by involving communal activities as the main strategy. The communal activities conducted include (1) cleaning the school environment, (2) waste management, (3) energy and water conservation, and (4) planting trees in the school garden. Through these activities, students are empowered to become individuals who are responsible for the environment and have a sense of care for cleanliness and the preservation of nature. In conclusion, the implementation strategy of Adiwiyata in elementary school 1 Bengkulu city through communal activities has successfully increased students' awareness of the importance of a clean and healthy environment. Communal activities serve as an effective means to build environmental consciousness and develop students' social attitudes. The implications of this research can contribute to the development of the Adiwiyata program and the implementation of communal approaches in character education in other schools.